Osteoid osteoma and osteoblastoma of the spine in children: features of intravertebral zoning and results of surgical treatment with a follow-up of at least one year - D.B. Malamashin; A.Yu. Mushkin (Хирургия позвоночника, 2024)
Objective. To analyze the features of zonal localization of osteoid osteoma and osteoblastoma and the results of their surgical treatment in pediatric patients. Material and Methods. The data of 41 children aged 4 to 17 years who underwent surgery for osteoid osteoma (29) and osteoblastoma (12) of the vertebrae were compared retrospectively within a monocentric cohort. The features of the tumor zonal location and the results of surgical treatment were assessed taking into account the risk of relapse and the need for instrumental stabilization. Results. Osteoid osteoma and osteoblastoma are localized in the posterior structures of the vertebrae (sectors 2–4 and 9–11 according to the Weinstein – Boriani – Biagini classification) in 93 and 75 %, respectively, with a predominance of right-sided localization of osteoid osteoma (sector 9–11). Osteoid osteomas are predominantly located in zones B and C, while the spread of osteoblastomas to zone D indicates a more aggressive course with the possibility of developing neurological symptoms in 50 % of cases. Complete removal of tumors in the volume of marginal resection due to unilateral localization in the posterior elements of the vertebra is safe and allows, in the absence of intraoperative destabilization, to complete the operation without additional instrumental fixation; local bone fusion is sufficient to prevent local instability. Conclusion. Osteoid osteoma and osteoblastoma of the vertebrae in children differ in localization, zoning according to the Weinstein – Boriani – Biagini classification, and clinical aggressiveness of the course. Features of intraorgan zoning of tumors with proximity to nerve structures limit the use of ablation technologies, while wide marginal resection provides a full-fledged cure. The need for instrumental stabilization of the spine depends on the volume of resection.